<span>To find a missing number in a data set given the mean of the data set, count the total number of data points in the data set, including the missing number, and multiply the mean by this total number. Next, add together the known numbers in the data set. Finally, take the difference of the two numbers just calculated.</span>
The short answer is that algebra doesn't work that way. You wouldn't divide *everything* by 2, but every term that contains a factor of 2.
In the expression
2 (6<em>x</em> - 1) + 2 (2<em>x</em> + 5)
both terms have a factor of 2 (the 2 out in front of them). They're the ones that get canceled when dividing by 2:
(2 (6<em>x</em> - 1) + 2 (2<em>x</em> + 5)) / 2 = 2/2 (6<em>x</em> - 1) + 2/2 (2<em>x</em> - 5)
… = 1 (6<em>x</em> - 1) + 1 (2<em>x</em> - 5)
… = (6<em>x</em> - 1) + (2<em>x</em> - 5)
and so on.
Looking ahead, it turns out that the equation is solved by <em>x</em> = 7. This makes 6<em>x</em> - 1 = 41 and 2<em>x</em> + 5 = 19. So the equation is saying that, if you make these replacements,
2×41 + 2×19 = 120
If you divide *everything* on the left by 2, you end up with fractions:
(2/2)×(41/2) + (2/2)×(19/2) = 41/2 + 19/2
but 41 + 19 = 60, so the end result would be 30, but that's not the same as 120/2 = 60.
Answer:No, because it does not pass the vertical line test.
Step-by-step explanation: